2017
DOI: 10.1080/15376516.2017.1357778
|View full text |Cite
|
Sign up to set email alerts
|

Responses of human hepatoma HepG2 cells to silver nanoparticles and polycyclic aromatic hydrocarbons

Abstract: The nanotechnology has revolutionized the global market with silver nanoparticles (AgNP) occupying a prominent position due to their remarkable anti-bacterial properties. However, there is no data about the adverse and toxic effects of associations of AgNP and ubiquitous compounds, such as polycyclic aromatic hydrocarbons (PAH). In the current study, we investigated the responses of HepG2 cells to realistic concentrations of AgNP (0.09, 0.9, and 9 ng ml) and mixture of PAH (30 and 300 ng ml), separately and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 80 publications
0
5
0
Order By: Relevance
“…If Ag(I) indeed blocked or slowed down Cu(I) export from hepatocytes via ATP7B, then one might consider the AgNPs effect on liver as sort of induced WD condition. A support for this supposition can be found in three independent studies of hepatocyte exposure to AgNPs, which found physiological and proteomic markers of oxidative stress [43][44][45]. Other possibilities include intracellular retention of both copper and silver by binding to copper chaperones and metallothioneins, and intracellular redistribution, e.g., to organelles via Copper transporter 2 Ctr2 [46].…”
Section: Discussionmentioning
confidence: 88%
“…If Ag(I) indeed blocked or slowed down Cu(I) export from hepatocytes via ATP7B, then one might consider the AgNPs effect on liver as sort of induced WD condition. A support for this supposition can be found in three independent studies of hepatocyte exposure to AgNPs, which found physiological and proteomic markers of oxidative stress [43][44][45]. Other possibilities include intracellular retention of both copper and silver by binding to copper chaperones and metallothioneins, and intracellular redistribution, e.g., to organelles via Copper transporter 2 Ctr2 [46].…”
Section: Discussionmentioning
confidence: 88%
“…While, to the best of our knowledge, no comparable proteomic study of silver nanoparticle effects in Hep G2 or similar human liver cells is available, the results of the present study are also well in line with previous data on silver nanoparticle toxicity in Hep G2 cells obtained with other methods. Cytotoxicity of nanosilver to Hep G2 cells has been demonstrated (Brkic Ahmed et al, ; Filipak Neto, Cardoso da Silva, Liebel, Voigt, & Oliveira Ribeiro, ) and, more importantly, available data provide strong evidence for a role of oxidative stress in Hep G2 cells exposed to nanoparticulate silver (Brzoska, Meczynska‐Wielgosz, Stepkowski, & Kruszewski, ; Filipak Neto et al, ). Moreover, a proliferative response, as suggested by bioinformatic analysis of our data, has been observed previously (Brzoska et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…The toxicity of silver NPs (AgNPs), cadmium-tellurium quantum dots (CdTeQDs), and silica NPs (SiO 2 NPs) has been described by us and others several times. AgNPs decreased the viability and proliferative potential of many cell types in culture, including human liver carcinoma HepG2 cells [3][4][5][6]. CdTeQDs also express significant toxicity, attributed mostly to their heavy metal components [7].…”
Section: Introductionmentioning
confidence: 99%